2021
DOI: 10.1016/j.artd.2021.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Hip Resurfacing vs Total Hip Arthroplasty in Patients Younger than 35 Years: A Comparison of Revision Rates and Patient-Reported Outcomes

Abstract: Background: Hip resurfacing arthroplasty (HRA) and total hip arthroplasty (THA) are two treatment options for end-stage degenerative hip conditions. The objective of this single-center retrospective cohort study was to compare implant survival and patient-reported outcomes (PROs) in young patients (35 years) who underwent HRA or THA. Methods: All patients aged 35 years or younger who underwent HRA or THA with a single high-volume arthroplasty surgeon between 2004 and 2015 were reviewed. The sample included 33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…published a 2019 cohort study showing better self-reported hip function scores with HR than with THA, primarily in scores of functions of daily living (90% vs 84%, respectively) and sport and recreation (77% vs 68%, respectively) [ 15 ]. One study evaluating HR vs THA in patients younger than 35 y showed excellent functional outcomes with both procedures and no statistical difference between patient-reported outcomes when comparing the 2 [ 16 ]. Another study demonstrated no differences in short-term outcomes when comparing the Oxford, the Western Ontario and McMaster Universities Osteoarthritis Index, and Harris Hip Scores, as well as the activity scores of young patients with HR vs a THA [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…published a 2019 cohort study showing better self-reported hip function scores with HR than with THA, primarily in scores of functions of daily living (90% vs 84%, respectively) and sport and recreation (77% vs 68%, respectively) [ 15 ]. One study evaluating HR vs THA in patients younger than 35 y showed excellent functional outcomes with both procedures and no statistical difference between patient-reported outcomes when comparing the 2 [ 16 ]. Another study demonstrated no differences in short-term outcomes when comparing the Oxford, the Western Ontario and McMaster Universities Osteoarthritis Index, and Harris Hip Scores, as well as the activity scores of young patients with HR vs a THA [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within five years, 9% (n=3) of patients in the THA group required revision due to complications such as instability (n=1), squeaking (n=1) or ceramic liner fracture (n=1), whereas no patients in the HRA group were revised. 50 Both HRA and THA resulted in significant improvements in PROMs, including the University of California, Los Angeles Activity (UCLAA) score (74% increase in both groups), modified Harris Hip score (HHS) (64% increase in HRA vs. 66% increase in THA), and Hip Dysfunction and Osteoarthritis Outcome Scores for Joint Replacement (49% increase in both groups). 50 Despite lower preoperative and postoperative PROMs in the THA group, the absolute improvements in these measures did not differ significantly between the two groups.…”
Section: How Does Hip Resurfacing Compare To Total Hip Arthroplasty?mentioning
confidence: 99%
“…50 Both HRA and THA resulted in significant improvements in PROMs, including the University of California, Los Angeles Activity (UCLAA) score (74% increase in both groups), modified Harris Hip score (HHS) (64% increase in HRA vs. 66% increase in THA), and Hip Dysfunction and Osteoarthritis Outcome Scores for Joint Replacement (49% increase in both groups). 50 Despite lower preoperative and postoperative PROMs in the THA group, the absolute improvements in these measures did not differ significantly between the two groups. The researchers concluded that both HRA and THA can be suitable surgical options for young patients.…”
Section: How Does Hip Resurfacing Compare To Total Hip Arthroplasty?mentioning
confidence: 99%
See 1 more Smart Citation
“…Registry data suggested that the choice of bearing surface and femoral-head size may also influence the risk of future revision 15 . Studies of contemporary THA performed without cement in patients <50 years of age have demonstrated rates of revision of 5% to 29% at intermediate-term follow-up 3,8,15-18 , with common failure modes including dislocation and aseptic loosening of the acetabular component.…”
mentioning
confidence: 99%